Laser a fibra dopada com Érbio com múltiplos comprimentos de onda e múltiplos regimes de operação simultâneos - Santos, Cláudia Barros dos (2011)
In this work, we inserted two Arrayed Waveguide Gratings (AWGs), in an Erbium doped fiber ring cavity laser, where a single gain medium at room temperature can emit laser in multiples wavelengths, simultaneous and individualy controlled. The setup allowed us to check different functions in the ring cavity. Here we show emission in CW regime, Passive Mode-Locking, using Carbon Nanotubes as saturable absorbers and finally Active mode-locking at 7GHz, simultaneously.